2015
DOI: 10.1088/1748-9326/10/6/064008
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of policy on consumer choices for private road passenger transport emissions reductions in six major economies

Abstract: The effectiveness of fiscal policy to influence vehicle purchases for emissions reductions in private passenger road transport depends on its ability to incentivise consumers to make choices oriented towards lower emissions vehicles. However, car purchase choices are known to be strongly socially determined, and this sector is highly diverse due to significant socio-economic differences between consumer groups. Here, we present a comprehensive dataset and analysis of the structure of the 2012 private passenger… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(64 citation statements)
references
References 11 publications
1
63
0
Order By: Relevance
“…It is also useful to illustrate the relationships between price, engine size and emissions for the South African vehicle market. It is assumed that vehicles with a larger engine size are typically more luxurious and expensive (Mercure & Lam, 2015). This property holds true for the South African data set as shown by the strong positive relationship between engine size and the logarithm of price in the first panel of Figure 3.…”
Section: Data Summarymentioning
confidence: 95%
See 4 more Smart Citations
“…It is also useful to illustrate the relationships between price, engine size and emissions for the South African vehicle market. It is assumed that vehicles with a larger engine size are typically more luxurious and expensive (Mercure & Lam, 2015). This property holds true for the South African data set as shown by the strong positive relationship between engine size and the logarithm of price in the first panel of Figure 3.…”
Section: Data Summarymentioning
confidence: 95%
“…For this reason, consumer choice modelling can be done successfully without considering fuel prices. Mercure and Lam (2015) also demonstrated that, even if consumers consider the lifetime fuel costs of vehicles at the time of purchase (under various discount rates), this cost is significantly lower than the initial investment of a vehicle purchase. Consequently, the fleet emissions reductions achieved per 1% tax on fuel are always smaller than equivalent tax rates on the vehicle purchase price.…”
Section: Fuel Price Considerationsmentioning
confidence: 99%
See 3 more Smart Citations